Economic policy and technological performance - Dasgupta, Partha; Stoneman, Paul.; Centre for Economic Policy Research (Great Britain) (Cambridge ; New York : Cambridge University Press, 1987)
A growing awareness of the contribution that technological change has made and can make to economic and social welfare has brought science and technology policy to the forefront of public discussions in both national and international forums. The papers in this volume, first presented at a Centre for Economic Policy Research conference held in London in September 1986 on the Economics of Technology Policy, represent a wide ranging contribution to the debate. Generally aimed at the non-specialist, the papers cover both the experience and application of policy as well as providing in-depth discussions of the rationale for intervention in the process of technological change. The authors include both policy-makers (Barber, Ergas and White) and the academic economists (Dasgupta, David, Griliches, Lyons, Pakes, Stiglitz and Stoneman). The volume will be of particular interest to policy-makers and their advisers concerned with technology-related issues and will contribute significantly to undergraduate and graduate courses in the same area.
Proceedings of a conference organized by the Centre for Economic Policy Research and held in London Sept. 1-2, 1986.
Includes bibliographies and index.
lje 25/08/16
Loans
Keywords: Technology and state; Technological innovations; Science and state